The role of self-efficacy in mediating the effects of transformational leadership and teacher competence on teacher performance at SMP Negeri 2 Dolok Masihul - Irpan Amin; Hasrudy Tanjung (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study examines the role of self-efficacy in mediating the effects of transformational leadership and teacher competence on teacher performance at SMP Negeri 2 Dolok Masihul. A quantitative approach with a cross-sectional design was employed, involving the entire population of 65 teachers through saturated sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results demonstrate that transformational leadership and teacher competence have positive and significant effects on both self-efficacy and teacher performance. Self-efficacy also has a positive and significant effect on teacher performance. The mediation analysis indicates that self-efficacy partially mediates the effects of transformational leadership and teacher competence on teacher performance, with indirect effect coefficients of 0.143 and 0.136, respectively. The research model explains 61.2 percent of the variance in self-efficacy and 71.4 percent of the variance in teacher performance. These findings highlight the importance of strengthening transformational leadership, professional competence, and teachers' confidence in their capabilities as complementary mechanisms for improving teacher performance.